2011
DOI: 10.2106/jbjs.j.00295
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes Following Single-Event Multilevel Surgery of the Upper Extremity for Children with Hemiplegic Cerebral Palsy

Abstract: Children with hemiplegic cerebral palsy showed significantly improved dynamic segmental alignment and, to a lesser degree, spontaneous use of the upper extremity following single-event multilevel surgery compared with a comparable nonoperative control group. However, the grasp-release ability did not significantly improve in either the operative or nonoperative group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 50 publications
0
42
0
Order By: Relevance
“…However, the assessment of spasticity or motor function in the upper limbs is preferable because defects in arm-hand performance due to stroke or CP lead to greater problems in daily life than defects involving the lower limbs (68). …”
Section: Introductionmentioning
confidence: 99%
“…However, the assessment of spasticity or motor function in the upper limbs is preferable because defects in arm-hand performance due to stroke or CP lead to greater problems in daily life than defects involving the lower limbs (68). …”
Section: Introductionmentioning
confidence: 99%
“…A summary of the included studies is presented in Table SI. The three prospective studies stated measurement time points in advance and two retrospective studies described the use of a standard protocol which included follow‐up time‐points . Five studies provided information about missing data and loss to follow‐up (Table SI) .…”
Section: Resultsmentioning
confidence: 99%
“…In all retrospective studies the risk of bias was critical for the items on selection (owing to lack of allocation concealment, loss to follow‐up), confounding (inherently to non‐controllable studies, different baseline characteristics), and measurement of outcomes (blinding of outcome assessment). Three studies were judged to be at serious risk of bias in at least one domain, but not at critical risk of bias in any domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Smitherman et al 34 , forty children with hemiplegic cerebral palsy who underwent upper-extremity single-event multilevel surgery were compared with twenty-six children who did not receive any upper-extremity interventions. On the basis of Shriners Hospital for Children Upper Extremity Evaluation, the authors concluded that singleevent multilevel surgery significantly improved dynamic segmental alignment and, to a lesser degree, spontaneous use of the upper extremity in comparison with nonoperative treatment.…”
Section: Upper Extremitymentioning
confidence: 99%